Comprehensive genetic characterization of rosette‐forming glioneuronal tumors: independent component analysis by tissue microdissection. (9th February 2017) - Kitamura, Yohei; Komori, Takashi; Shibuya, Makoto; Ohara, Kentaro; Saito, Yuko; Hayashi, Saeko; Sasaki, Aya; Nakagawa, Eiji; Tomio, Ryosuke; Kakita, Akiyoshi; Nakatsukasa, Masashi; Yoshida, Kazunari; et al.
Abstract: A rosette‐forming glioneuronal tumor (RGNT) is a rare mixed neuronal‐glial tumor characterized by biphasic architecture of glial and neurocytic components. The number of reports of genetic analyses of RGNTs is few. Additionally, the genetic background of the unique biphasic pathological characteristics of such mixed neuronal‐glial tumors remains unclear. To clarify the genetic background of RGNTs, we performed separate comprehensive genetic analyses of glial and neurocytic components of five RGNTs, by tissue microdissection. Two missense mutations in FGFR1 in both components of two cases, and one mutation in PIK3CA in both components of one case, were detected. In the latter case with PIK3CA mutation, the additional FGFR1 mutation was detected only in the glial component. Moreover, the loss of chromosome 13q in only the neurocytic component was observed in one other case. Their results suggested that RGNTs, which are tumors harboring two divergent differentiations that arose from a single clone, have a diverse genetic background. Although previous studies have suggested that RGNTs and pilocytic astrocytomas (PAs) represent the same tumor entity, their results confirm that the genetic background of RGNTs is not identical to that of PA.